TLR7 modulating B-cell immune responses in the spleen of C57BL/6 mice infected with Schistosoma japonicum - Wei, Haixia; Xie, Hongyan; Qu, Jiale; Xie, Anqi; Xie, Shihao; Huang, He; Li, Jiajie; Fang, Chao; Shi, Feihu; Qiu, Huaina; Qi, Yanwei; Tian, Xu; et al. (PLOS Neglected Tropical Diseases, 2021)
Author summary Schistosomiasis seriously jeopardizes public health and social development in tropical and subtropical regions. B cells play an important role in Schistosoma infection-induced diseases. TLR7 is an intracellular member of the innate immune receptor. The role of TLR7 on B cells mediated immune response is still unclear. Here, we found the percentage and numbers of B cells increased in the infected mice (p < 0.05), and the expression of many activation and function associated molecules were also changed on B cells. B cells were served as the main cell population expressed TLR7. When TLR7 gene was knockout, the soluble egg antigen (SEA) specific antibody and activation associated molecules were decreased in S. japonicum infected mice. Additionally, SEA could induce the activation of B cells by TLR7. Finally, we found the effects of TLR7 on B cells are dependent on the activation of NF-κB p65. In this study, the characteristic of B cells in the spleen of S. japonicum infected C57BL/6 mice was explored, and the role of TLR7 on the progress of B cell activation and differentiation was investigated.